Analisis pengaruh manajemen strategi dan risiko terhadap kinerja perbankan syariah - Rushady, Fijar Rahmawan (Maliki Interdisciplinary Journal, 2025)
This research purposed to investigate the impact of strategic management and risk management on the performance of Islamic banking. The study utilizes literature review with descriptive analysis in investigating the connection between Sharia-compliant business strategy implementation and financial as well as compliance risks management. The findings show that successful strategic management and total risk management are important for enhancing operating performance and establishing customer confidence in Islamic banks. Merging the two elements not only motivates business sustainability but also enhances the competitiveness of Islamic banks in a more competitive Islamic financial market. The findings of the research highlight the need to enhance both fields of management in order to meet the opportunities and challenges of the Islamic financial market.